EFFECTS OF HIGH-FLOW NASAL CANNULA IN THE POSTOPERATIVE PERIOD OF PEDIATRIC CARDIAC SURGERY: SCOPING REVIEW - Amorim Bonfim, Mariany; Vitória Brito dos Santos, Jéssica; Nunes Veiga, Isis (Health and Society, 2025)
INTRODUCTION: The use of High Flow Nasal Cannula (HFNC) in children after cardiac surgery may offer benefits that are observed based on blood gas analysis, vital signs and a reduction in the reintubation rate. The use begins with a clinical picture of acute respiratory failure culminating in the presence of some symptoms. The use of HFNC improves the respiratory condition after extubation and mainly by preventing extubation failures, reducing reintubation rates and preventing atelectasis. OBJECTIVE: To map the hemodynamic and clinical effects of High Flow Nasal Cannula in the postoperative period of pediatric cardiac surgery. METHODS: Scoping review that followed the PRISMA-ScR recommendations, using the PubMed, SciELO, Virtual Health Library, Lilacs, PEDro, Embase and Cochrane Library databases. Articles that evaluated the hemodynamic and clinical effects of HFNC in the postoperative period of cardiac surgeries were included and articles in which children had comorbidities associated with heart disease, reviews, case reports, opinion articles and articles that were not available in full were excluded. RESULTS: six articles addressed and analyzed relevant hemodynamic and clinical outcomes, such as PaO2, PCO2, SpO2, PaO2/FiO2, BP, HR, RR, CEC, treatment failure, extubation failure, reintubation rate, length of hospital stay or ICU stay, and atelectasis rate. CONCLUSION: The findings of this study indicate a tendency for the therapy analyzed to contribute to the improvement of PaO2, PCO2, reintubation rate and reduction of hospital stay in the postoperative period of pediatric cardiac surgery.